2017
DOI: 10.1371/journal.pone.0178671
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and attitudes towards hepatitis B and its transmission from mother to child among pregnant women in Guangdong Province, China

Abstract: BackgroundHepatitis B virus (HBV) infection remains a serious public health problem worldwide. Mother-to-child transmission (MTCT) of HBV is the major mode of transmission in HBV-endemic areas, including China, where little is known about pregnant women’s knowledge of and attitudes towards HBV infection and MTCT.MethodsA cross-sectional survey, conducted in pregnant women in Guangdong Province, China, measured HBV knowledge and attitudes using a questionnaire, at one tertiary and two rural hospitals.ResultsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
48
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 22 publications
12
48
6
1
Order By: Relevance
“…The current finding showed that 73.4% of the participants had poor knowledge, whereas another study conducted in eastern Ghana in 2016 showed that 40.2% of pregnant women had good knowledge [11]. In addition, in a crosssectional study conducted in China in 2017, only 21% of the participants were able to answer all the general knowledge-related questions correctly [7]. Similarly, a study conducted in Ghana in 2014 revealed that less than half of the participants (46.2%) knew about hepatitis B infection and its disease [13].…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…The current finding showed that 73.4% of the participants had poor knowledge, whereas another study conducted in eastern Ghana in 2016 showed that 40.2% of pregnant women had good knowledge [11]. In addition, in a crosssectional study conducted in China in 2017, only 21% of the participants were able to answer all the general knowledge-related questions correctly [7]. Similarly, a study conducted in Ghana in 2014 revealed that less than half of the participants (46.2%) knew about hepatitis B infection and its disease [13].…”
Section: Discussioncontrasting
confidence: 50%
“…But a high rate of good practice was reported (42.7%) from Addis [25]. On the other hand, reports from Addis Ababa, Ethiopia [14], and Guangdong Province, China [7], showed that higher education level was associated with better knowledge and attitude scores. Likewise, religion was significantly associated with attitude and practice (P < 0:001), while occupation was only associated with practice (P < 0:001).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This survey showed that pregnant women and mothers in Vietnam's Quang Ninh and Hoa Binh provinces lacked knowledge regarding HBV transmission and prevention regardless of age, education, economic condition and childbearing status. Limited knowledge regarding HBV among pregnant women is consistent with findings from previous studies in other high epidemic countries [11][12][13]. Multivariable analysis showed that mothers who received HBV information during pregnancy consistently had better knowledge regarding HBV transmission, prevention and immunization than who did not.…”
Section: Discussionsupporting
confidence: 87%
“…Disease Control and Prevention based on their past experience and a literature review of comparable studies [21][22][23]. A series of question were listed with point for each question, and zero for ignorance or mistake.…”
Section: Questionnaire Designmentioning
confidence: 99%